Numerical Simulation of Heat-pipe Radiator for Metro Vehicle Converter - DING Jie; TANG Yutu (Kongzhi Yu Xinxi Jishu)
With heat-pipe radiator and air-cooling in driving state, structure of converter cabinet can be simplified. In order to analyze the thermal performance of heat-pipe radiator, velocity and temperature distribution are analyzed by Fluent software. Results show that heat-pipe radiator still has predominated performance at slowly driving velocity. The veracity of simulation results are verified by practical applications.